Sosio Regligious Teks Persubakan Anggabaya Denpasar Timur Dalam Perspektif Ekolinguistik - Antari, Ni Made Suwari; Suparwa, I Nyoman; Sudipa, I Nengah; Satyawati, Made Sri (Bumi Lestari; Vol 24 No 1 (2024), 2024)
Activities in the subak area display close integration between ritual patterns and agricultural procedures. This research aims to reveal socio-religious ideology in the Anggabaya East Denpasar subak’s texts. Research methods include the matching method and the agih method, with data obtained through interviews and direct observation of several respondents taken by sampling. In this subak, farmers practice high respect for God Vishnu and Dewi Sri, considered to be the givers of prosperity in the rice fields. Work in the rice fields is not only done physically but is also based on a religious aspect full of offerings and prayers. For example, farmers pray to Ratu Betara Sri, asking for safety when working in the rice fields by offering biukukung offerings. The agricultural process is directed through ritual stages, including ceremonies for rat pests. The farmer conveyed a prayer to Jero Ketut, begging the rats not to disturb him and asking for safety, "niki tiang nawegang ring jero ketut niki, ampunang ngusak asik, titiang nunas keselametan, mangde mekaon." Overall, the existence of religious and ritual elements in subak reflects the strong connection between spirituality and agricultural activities, creating harmony in the life of an agricultural society.